2012
DOI: 10.1007/s10620-012-2460-5
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Gene Polymorphisms in Cytokines and Toll-Like Receptors with Higher Risk for Gastric Cancer

Abstract: Our findings evidenced that the combined effect of polymorphisms in genes involved in the inflammatory process may potentiate the risk of gastric cancer, thus emphasizing the importance of evaluating multiple polymorphisms together.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 56 publications
0
31
0
Order By: Relevance
“…Among the TNF-α-308 G/A and -857 C/T SNPs evaluated in this study, only TNF-α-857 C/T was found to be associated with gastric cancer. Several studies have reported the same association [9,20,[40][41][42][43], but studies attempting to associate cytokine expression with the presence of SNPs are uncommon [7].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Among the TNF-α-308 G/A and -857 C/T SNPs evaluated in this study, only TNF-α-857 C/T was found to be associated with gastric cancer. Several studies have reported the same association [9,20,[40][41][42][43], but studies attempting to associate cytokine expression with the presence of SNPs are uncommon [7].…”
Section: Discussionmentioning
confidence: 94%
“…Examples of these polymorphisms include IL-1β, IL-1RN, IL-8, TNF-α, and IL-10, which may contribute to variations in the risk of developing gastric cancer [1,[4][5][6]. Some SNPs that occur within regulatory regions of cytokine genes are believed to be involved in changes to the affinity of transcription factors, and they therefore affect the cytokine expression and secretion profile in response to agents of infection [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…62 Studies in different populations revealed association between individual's carriers of the allele 2 and increased risk of developing chronic gastritis, gastric ulcer and gastric cancer. 63,64 IL-6 is a pro-inflammatory cytokine that acts as an inflammatory mediator and endocrine regulator, playing an important role in host defense mechanisms as a messenger between innate and adaptive systems. 65 Moreover, it is involved in the regulation of various cellular functions, such as, proliferation, apoptosis and angiogenesis.…”
Section: 7879mentioning
confidence: 99%
“…(2) A population genetics approach Table 3 Genotype and allele frequencies, odds ratio, confidence interval, and p value of the logistic regression analysis with and without the covariates sex, age, Native American ancestry, socioeconomic (first factor), symptoms (second factor), and nutritional (third factor) information, using additive, dominant, and recessive model (3) Although controlling for ancestry is critical for variants that have different allele frequencies in Native Americans, Europeans, and Africans, ancestry (estimated with enough accuracy) is frequently ignored in candidate-gene association studies in Latin American populations [45]. (4) Although we did not find association between the tested SNPs and gastric cancer in the population from Lima with high Native American ancestry, meta-analyses suggest that IL8-rs4073-A and PTGS2-rs689466-A are susceptibility variants for gastric cancer in Asia.…”
Section: Effect Of Promoter Haplotype On Il8rb Transcriptional Activamentioning
confidence: 99%